An Analysis of Phonological Mistake in the YouTube “Vior dan Vincent Bertemu Satpam GI” on Raditya Dika Channel - Diana Tri Widarti; Martius Martius; Rina Fitriani; Vera Sardila; Welli Marlisa (Gurindam: Jurnal Bahasa dan Sastra, 2025)
This study aims to describe the pronunciation mitake in Youtube “Vior dan Vincent Bertemu Satpam GI”. Data were collected using the listening and note-taking methods, then analyzed using insertion, deletion, and replacement techniques. Furthermore, the following conclusions were obtained: (1) mistake in the form of phoneme changes, consisting of (a) vowel pronunciation mistake, (b) consonant pronunciation mistakes, (2) mistake due to phoneme omissions consisting of (a) omission of the phoneme /h/ in the onsed and coda positions, (b) omission of the phoneme /s/ in the consoant cluster /ks/, and omission of the phoneme /k/ in the consonant cluster /ks/; (3) mistake in the form of added phonemes, namely the addition of the phoneme /n/ in the nucleus position of the word.